2022
DOI: 10.3389/fphar.2022.1082997
|View full text |Cite
|
Sign up to set email alerts
|

The adenosine A2A receptor antagonist KW6002 distinctly regulates retinal ganglion cell morphology during postnatal development and neonatal inflammation

Abstract: Adenosine A2A receptors (A2ARs) appear early in the retina during postnatal development, but the roles of the A2ARs in the morphogenesis of distinct types of retinal ganglion cells (RGCs) during postnatal development and neonatal inflammatory response remain undetermined. As the RGCs are rather heterogeneous in morphology and functions in the retina, here we resorted to the Thy1-YFPH transgenic mice and three-dimensional (3D) neuron reconstruction to investigate how A2ARs regulate the morphogenesis of three mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Accordingly, alterations of astrocytic morphology critically affect the ability of astrocytes to control synaptic plasticity and memory (Liao et al, 2017;Popov et al, 2020;Tanaka et al, 2013;reviewed in Lawal et al, 2022) and we previously reported a reduction of LTP amplitude coupled with an increase in astrocytic tridimensional complexity triggered by a gliotoxin (Pereira et al, 2021). This prompts the possibility that astrocytic A 2A R may control synaptic plasticity and memory through a remodeling of astrocytic morphology, in accordance with the previously reported ability of A 2A R to control microtubule polarization (Edmunds et al, 2022) and cellular remodeling (Alçada-Morais et al, 2021;Hu et al, 2022;Ribeiro et al, 2016;Xu et al, 2022), namely of microglia (Caetano et al, 2017;Simões-Henriques et al, 2020) and reactive astrocytes (Brambilla et al, 2003). However, it still remains to be defined which of the numerous transducing systems (Dias et al, 2022;Doengi et al, 2008: Kanno & Nishizaki, 2012Ke et al, 2009Ke et al, , 2012 and genetic reprograming pathways (see Paiva et al, 2019) operated by A 2A R in astrocytes are responsible for the morphological remodeling of astrocytes.…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, alterations of astrocytic morphology critically affect the ability of astrocytes to control synaptic plasticity and memory (Liao et al, 2017;Popov et al, 2020;Tanaka et al, 2013;reviewed in Lawal et al, 2022) and we previously reported a reduction of LTP amplitude coupled with an increase in astrocytic tridimensional complexity triggered by a gliotoxin (Pereira et al, 2021). This prompts the possibility that astrocytic A 2A R may control synaptic plasticity and memory through a remodeling of astrocytic morphology, in accordance with the previously reported ability of A 2A R to control microtubule polarization (Edmunds et al, 2022) and cellular remodeling (Alçada-Morais et al, 2021;Hu et al, 2022;Ribeiro et al, 2016;Xu et al, 2022), namely of microglia (Caetano et al, 2017;Simões-Henriques et al, 2020) and reactive astrocytes (Brambilla et al, 2003). However, it still remains to be defined which of the numerous transducing systems (Dias et al, 2022;Doengi et al, 2008: Kanno & Nishizaki, 2012Ke et al, 2009Ke et al, , 2012 and genetic reprograming pathways (see Paiva et al, 2019) operated by A 2A R in astrocytes are responsible for the morphological remodeling of astrocytes.…”
Section: Discussionsupporting
confidence: 89%
“…KW6002 had bidirectional effects on dendritic complexity of Type I and III RGCs and altered their morphologies. Under neonatal inflammation, KW6002 increased the proportion of Type I and II RGCs with specific changes in their morphology [ 102 ]. Table 1 shows the main recent studies investigating the effects of AR ligands in in vivo models of CNS pathology.…”
Section: Ars In Cns Diseasesmentioning
confidence: 99%